EVALUASI KRIM DENGAN VARIASI KONSENTRASI EKSTRAK BIJI LADA HITAM (Piper nigrum L.) - Yulius Evan Christian; Senny Listy Kartika Falestin; Pra Panca Bayu Chandra; Nia Lisnawati; Mega Efrilia; Pricillya Maria Loimalitna; Indah Nur El Hasanah (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2025)
Black pepper (Piper nigrum L.) is a medicinal plant that contains active compounds such as piperine, flavonoids, and essential oils, which are known to exhibit anti-inflammatory, antioxidant, and antimicrobial properties. This study aims to evaluate the physical quality of cream formulations containing varying concentrations of 96% ethanol extract of black pepper seeds. A descriptive experimental method was employed, focusing on the assessment of organoleptic properties, homogeneity, pH, spreadability, adhesion, and viscosity over a four-week storage period. Four formulations were tested: F0 as a control without extract, F1 with 1% extract, F2 with 2%, and F3 with 3%. The evaluation results showed that all formulations met the required physical quality standards. The creams retained stable color and odor, demonstrated uniform ingredient distribution, and had pH values within the safe range for topical application (4.5–6.5). The spreadability and adhesion properties were within ideal criteria, and viscosity levels ranged between 2000 and 5000 cP, indicating suitable consistency. Among the tested formulations, F2 exhibited the most optimal performance in terms of physical stability and user comfort. Based on these findings, it can be concluded that black pepper seed extract is suitable for formulation into a topical cream preparation, with the 2% concentration showing promising potential for development as a natural-based, safe, and effective topical product.